Community based treatment for chronic oedema: an effective service model - Moffatt, Christine J.; Doherty, Debra; Franks, Peter J.; Mortimer, Peter (Mary Anne Liebert, 2017)
BACKGROUND: Chronic oedema care is patchy and of variable quality internationally. This study was undertaken to develop and evaluate a system of care that would provide for patients within a geographical area of London (Wandsworth), UK. METHODS AND RESULTS: A prospective cohort design with intervention of a new service design following a six month baseline period. Patients were identified through health professionals. A stratified random sample was drawn from all patients and an implementation strategy developed. Clinical assessment combined with questionnaires evaluated clinical, patient and health service outcomes at six monthly periods. In all, 312 patients were identified in community and acute services giving a crude ascertainment rate of 1.16 per 1,000 population. The random sample of 107 was mostly female (82%) with mean (SD) age of 72.9 (12.4) in men and 68.6 (15.0) years in women. Mean reductions in limb volume achieved statistical differences at 6-12 months after implementation (difference [d] =115 ml, p=0.0001). Incidence of cellulitis dropped from 41.5/ 100 patient years at baseline to zero at 6-12 months. Quality of life showed greatest improvements between baseline and 6 months post implementation, the largest differences being in role physical (d=32.7, p=0.0001) and role emotion (d=24.0, p<0.0001). Euroqol increased following implementation by a mean score of 0.05 (p=0.007). There was a in six monthly health care costs from £50171 per100 patients at baseline to £17618 between 6 and 12 months.